Stations (maqamat) and states (ahwal) in the context of humanity studies: dialogical encounter of spirituality and the psychology of religion - Widodo, Aris; Hayatuddin, Akh. Kholis; Farmawati, Cintami; Sidik, Sidik (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2023)
Grounding on Ian Graeme Barbour’s (1923-2013) typology of relationships between science and religion, this article addresses the issue of the spiritual journey, with special reference to the discourse of stations (maqa>ma>t) and states (ahwa>l), in the context of humanity study, that is, psychology of religion. According to Barbour, there are four types of relations between science and religion, namely conflict, independence, dialogue, and integration. Following the tendency of the third and the fourth relationships of science and religion, this study argues that there exists a melting point of spirituality, in this regard stations and states of spiritual journey, on the one hand, and psychology of religion, on the other. In this light, this article strengthens the illustrative studies on dialogical encounters between spirituality, in the field of mystical philosophy, and the psychology of religion, in the context of humanity studies.